دراسة قياسية لتأثير وسببية العمق المالي على القطاع الحقيقي في الجزائر للفترة (1990-2019) - رزقي, وائل; ديب, كمال (جامعة الوادي - University of Eloued, 2021)
This paperaims to examine the impact and causality of financialdepth on the real sector in Algeriabased on annualdata obtainedfrom the World Bank database for the period (1990-2019) using the ARDL approach and the Granger causality test. One of the more significant findings to emerge from this study is that the financial depth has an opposite effect on the real sector and is not direct, whereas the results of the causality of the Granger test revealed the existence of a one-way causal relationship that starts from the real sector and goes to the financial depth. Perhaps these results confirm and reflect the financial shallowness of the Algerian economy.
A standard study of the effect and causation of financial depth on the real sector in Algeria for the period(2019-1990)
مقال
Keywords: العمق المالي؛ القطاع حقيقي؛ مقاربة ARDL؛ سببية غرانجر؛ الاقتصاد جزائري